Studies of modern Italian dog populations reveal multiple patterns for domestic breed evolution - Talenti; Dreger, Dayna L.; Dayna L.; Frattini; Stefano; Polli; Michele; Marelli; Harris, Alexander C.; Liotta, Luigi; Cocco, Raffaella; Hogan, Andrew N.; et al. (Ecology and Evolution, 2018)
Through thousands of years of breeding and strong human selection, the dog (Canis lupus familiaris) exists today within hundreds of closed populations throughout the world, each with defined phenotypes. A singular geographic region with broad diversity in dog breeds presents an interesting opportunity to observe potential mechanisms of breed formation. Italy claims 14 internationally recognized dog breeds, with numerous additional local varieties. To determine the relationship among Italian dog populations, we integrated genetic data from 263 dogs representing 23 closed dog populations from Italy, seven Apennine gray wolves, and an established dataset of 161 globally recognized dog breeds, applying multiple genetic methods to characterize the modes by which breeds are formed within a single geographic region. Our consideration of each of five genetic analyses reveals a series of development events that mirror historical modes of breed formation, but with variations unique to the codevelopment of early dog and human populations. Using 142,840 genome-wide SNPs and a dataset of 1,609 canines, representing 182 breeds and 16 wild canids, we identified breed development routes for the Italian breeds that included divergence from common populations for a specific purpose, admixture of regional stock with that from other regions, and isolated selection of local stock with specific attributes.